Pathogenesis of Hypertrophic Cardiomyopathy is Mutation Rather Than Disease Specific: A Comparison of the Cardiac Troponin T E163R and R92Q Mouse Models - Cecilia Ferrantini; Raffaele Coppini; Josè Manuel Pioner; Francesca Gentile; Benedetta Tosi; Luca Mazzoni; Beatrice Scellini; Nicoletta Piroddi; Annunziatina Laurino; Lorenzo Santini; Valentina Spinelli; Leonardo Sacconi; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2017)
BackgroundIn cardiomyocytes from patients with hypertrophic cardiomyopathy, mechanical dysfunction and arrhythmogenicity are caused by mutation‐driven changes in myofilament function combined with excitation‐contraction (E‐C) coupling abnormalities related to adverse remodeling. Whether myofilament or E‐C coupling alterations are more relevant in disease development is unknown. Here, we aim to investigate whether the relative roles of myofilament dysfunction and E‐C coupling remodeling in determining the hypertrophic cardiomyopathy phenotype are mutation specific. Methods and ResultsTwo hypertrophic cardiomyopathy mouse models carrying the R92Q and the E163R TNNT2 mutations were investigated. Echocardiography showed left ventricular hypertrophy, enhanced contractility, and diastolic dysfunction in both models; however, these phenotypes were more pronounced in the R92Q mice. Both E163R and R92Q trabeculae showed prolonged twitch relaxation and increased occurrence of premature beats. In E163R ventricular myofibrils or skinned trabeculae, relaxation following Ca2+ removal was prolonged; resting tension and resting ATPase were higher; and isometric ATPase at maximal Ca2+ activation, the energy cost of tension generation, and myofilament Ca2+ sensitivity were increased compared with that in wild‐type mice. No sarcomeric changes were observed in R92Q versus wild‐type mice, except for a large increase in myofilament Ca2+ sensitivity. In R92Q myocardium, we found a blunted response to inotropic interventions, slower decay of Ca2+ transients, reduced SERCA function, and increased Ca2+/calmodulin kinase II activity. Contrarily, secondary alterations of E‐C coupling and signaling were minimal in E163R myocardium. ConclusionsIn E163R models, mutation‐driven myofilament abnormalities directly cause myocardial dysfunction. In R92Q, diastolic dysfunction and arrhythmogenicity are mediated by profound cardiomyocyte signaling and E‐C coupling changes. Similar hypertrophic cardiomyopathy phenotypes can be generated through different pathways, implying different strategies for a precision medicine approach to treatment.